Exploring the education in cultural competence and transcultural care in Spanish for nurses and future nurses: a scoping review and gap analysis - Yasmin El-Messoudi; Manuel Lillo-Crespo; Juan Leyva-Moral (BMC, 2023)
Abstract Background Globalization and population migration have led to increasingly culturally diverse societies, which has made nursing education in cultural competence and transcultural care a priority. This includes the ability to provide person-centered and culturally congruent care, even within one's own culture. However, this sort of training has been developed and implemented in practice comparatively more by English-speaking societies. Therefore, the aim of this study was to identify the existing educational initiatives for nurses and future ones in cultural competence and transcultural care in Spanish and explore their didactic characteristics in terms of teaching and learning formats, contents, skills, and evaluation methods at different academic levels. Methods A scoping review was carried out by following the specific PRISMA recommendations and those of the Joanna Briggs Institute guidance throughout PudMed, Web of Science, Embase, Google Scholar, and Cinahl databases and also gray literature in the form of official documentation that later was complemented with a gap analysis including training programs published by Spanish and Latin-American educational institutions and the approaches of key academic informants. Results The published evidence on nursing training in cultural competence or related topics in Spanish-speaking higher education for nurses is limited. Specific nursing programs in Spanish-speaking universities are primarily found in Spain, with fewer options available in Latin America. These contents are offered either as optional subjects or immersed in other courses and mainly taught in theoretical sessions. Practice in real contexts is supposed to be evaluated transversally under the cultural scope according to national educational recommendations though barely visible in students' evaluation reports. Even though postgraduate training dedicated to these issues exists, it is still limited, mixed with other contents, and generally depends on a few researchers investigating and publishing on the topic from very specific universities. Conclusions It is essential to establish a common global strategy including Spanish-speaking countries in nurses' higher education and professional training on topics focused on cultural competence as well as the provision of nurses' social and cultural sensitivity towards their own culture and to define whether those that currently exist are effective. It is also crucial that this training was evaluated in practice in order to achieve enough impact on students, health organizations, and population health.